How small is enough for the left heart decompression cannula during extracorporeal membrane oxygenation? - Sua Kim; Jin Seok Kim; Jae Seung Shin; Hong Ju Shin (Acute and Critical Care, 2019)
Background Left ventricular (LV) distension is a recognizable problem accompanied by subsequent complications during venoarterial extracorporeal membrane oxygenation (VA-ECMO). However, no gold standard for LV decompression has been established, and no minimal flow requirement has been designated. Thus, we evaluated the efficacy of the 8-Fr Mullins sheath for left heart decompression during VA-ECMO in adult patients. Methods Left heart decompression was performed when severe pulmonary edema was detected on chest radiography or when no generation of pulse pressure followed severe LV dysfunction in patients receiving VA-ECMO. We punctured the interatrial septum and inserted an 8-Fr Mullins sheath into the left atrium via the femoral vein. The sheath was connected to the venous catheter used for ECMO. The catheter was maintained during VA-ECMO. Results The left heart decompression procedure was performed in seven of 35 patients who received VA-ECMO between February 2017 and June 2018. Three patients had acute myocardial infarction; three, fulminant myocarditis; and one, dilated cardiomyopathy. Four patients showed noticeable improvement of pulmonary edema within 3 days, and three patients with a pulse pressure of <10 mm Hg showed an increase in pulse pressure of >20 mm Hg within 24 hours from the left heart decompression procedure. All seven patients were successfully weaned from VA-ECMO. No complications related to the left heart decompression procedure occurred. Conclusions An 8-Fr sheath may be a possible option for left heart decompression in adult patients with LV distension under VA-ECMO who are expecting recovery of LV function.